2014
DOI: 10.1002/masy.201400017
|View full text |Cite
|
Sign up to set email alerts
|

In‐Line Monitoring of Size Distributions in Liquid‐Liquid Dispersions and Suspension Polymerizations by Focused Beam Reflectance Measurements

Abstract: Summary This work studies the use of Focused Beam Reflectance Measurements (FBRM) for monitoring of size distributions in liquid‐liquid (styrene‐water) dispersions and styrene suspension polymerizations performed in stirred tanks. The effects of the suspending agent concentration, stirring rate and presence of external light sources on the FBRM performance were evaluated during the in‐line monitoring of average size chords and chord length distribution (CLD). It can be stated that FBRM is sensitive to variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…F ocused beam reflectance measurement (FBRM) is a measurement technique that allows for in-situ dynamic measurements of particle or drop sizes in a process. The FBRM probe is used extensively in crystallization processes and a number of processes with a solid dispersed phase, [1][2][3][4][5][6][7] as well as in the study of liquid/liquid dispersions [7][8][9][10][11][12] and more recently it has been applied to crude oil systems. [13][14][15][16][17][18] The FBRM probe directs a laser beam through a sapphire window into the fluid and collects backscattered light.…”
Section: Introductionmentioning
confidence: 99%
“…F ocused beam reflectance measurement (FBRM) is a measurement technique that allows for in-situ dynamic measurements of particle or drop sizes in a process. The FBRM probe is used extensively in crystallization processes and a number of processes with a solid dispersed phase, [1][2][3][4][5][6][7] as well as in the study of liquid/liquid dispersions [7][8][9][10][11][12] and more recently it has been applied to crude oil systems. [13][14][15][16][17][18] The FBRM probe directs a laser beam through a sapphire window into the fluid and collects backscattered light.…”
Section: Introductionmentioning
confidence: 99%
“…However, the applications of FBRM and ORM techniques in the suspension polymerization are rare. Recently, Poblete et al . employed FBRM for inline monitoring of liquid–liquid (styrene–water) dispersions and styrene suspension polymerizations and found that FBRM is capable of monitoring the initial particle breakage stage and the attainment of the final breakage/coalescence equilibrium in dispersion experiments, and coalescence stage in suspension polymerizations.…”
Section: Introductionmentioning
confidence: 99%